Compact and full-range carbon dioxide sensor using photoacoustic and resonance dependent modes - Yifan Li; Lixian Liu; Liang Zhao; Xueshi Zhang; Le Zhang; Jialiang Sun; Huiting Huan; Yize Liang; Jiyong Zhang; Xiaopeng Shao; Andreas Mandelis; Roberto Li Voti (Photoacoustics)
A compact and robust optical excitation photoacoustic sensor with a self-integrated laser module excitation and an optimized differential resonator was developed to achieve high sensitivity and full linear range detection of carbon dioxide (CO2) based on dual modes of wavelength modulated photoacoustic spectroscopy (WMPAS) and resonant frequency tracking (RFT). The integrated laser module equipped with three lasers (a quantum cascade laser (QCL), a distributed feedback laser (DFB) and a He-Ne laser) working in a time-division multiplexing mode was used as an integrated set of spectroscopic sources for detection of the designated concentration levels of CO2. With the absorption photoacoustic mode, the WMPAS detection with the QCL and DFB sources was capable of CO2 detection at concentrations below 20 %, yielding a noise equivalent concentration (NEC) as low as 240 ppt and a normalized noise equivalent absorption coefficient (NNEA) of 4.755 × 10−10 W cm−1/√Hz, and dynamic range as great as 11 orders of magnitude. Higher concentration detection ranges (20 %-100 %) of CO2 were investigated using the RFT mode with an amplitude-stabilized He-Ne laser and a mechanical chopper. With the dual modes of WMPAS and RFT, the optical excitation sensor achieved full-range CO2 detection, with an R² ≥ 0.9993 and a response time of 5 seconds. The compact and full-range CO2 sensor combines the advantages of WMPAS and RFT and offers a solution for high sensitivity, linearity and full-range CO2 detection.